2017
DOI: 10.1007/s10827-017-0662-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term depression and transient memory in sensory cortex

Abstract: Persistent neuronal activity is usually studied in the context of short-term memory localized in central cortical areas. Recent studies show that early sensory areas also can have persistent representations of stimuli which emerge quickly (over tens of milliseconds) and decay slowly (over seconds). Traditional positive feedback models cannot explain sensory persistence for at least two reasons: (i) They show attractor dynamics, with transient perturbations resulting in a quasi-permanent change of system state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…NTA requires STP and recurrent inhibition, whose role on network dynamics have been studied in the past. Yet, STP was mainly examined in the context of stable working memory in recurrent networks (Mongillo et al, 2008; Zenke et al, 2015; Seeholzer et al, 2019) and transient delay activity following stimulus offset (Hempel et al, 2000; Gillary et al, 2017). However, its role in generating strongly amplified onset transients as a possible coding paradigm was largely ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NTA requires STP and recurrent inhibition, whose role on network dynamics have been studied in the past. Yet, STP was mainly examined in the context of stable working memory in recurrent networks (Mongillo et al, 2008; Zenke et al, 2015; Seeholzer et al, 2019) and transient delay activity following stimulus offset (Hempel et al, 2000; Gillary et al, 2017). However, its role in generating strongly amplified onset transients as a possible coding paradigm was largely ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Computationally, Hebbian cell assemblies can amplify specific activity patterns through positive feedback, also referred to as Hebbian amplification. Based on these principles, several studies have shown that Hebbian amplification can drive persistent activity that outlasts a preceding stimulus (Hopfield, 1982; Amit and Brunel, 1997; Yakovlev et al, 1998; Wong and Wang, 2006; Zenke et al, 2015; Gillary et al, 2017), comparable to selective delay activity observed in the prefrontal cortex when animals are engaged in working memory tasks (Funahashi et al, 1989; Romo et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Grant Gillary discovered that short-term depression, which is ubiquitous among cortical neurons, can create short-term persistence in derivative feedback circuits. If short-term depression acts differentially on positive and negative feedback projections between two coupled neurons, they can change their time constant dynamically, allowing for fast onset and slow decay (Gillary et al, 2017).…”
Section: Persistencementioning
confidence: 99%
“…Computationally, Hebbian cell assemblies can amplify specific activity patterns through positive feedback, also referred to as Hebbian amplification. Based on these principles, several studies have shown that Hebbian amplification can drive persistent activity that outlasts a preceding stimulus ( Hopfield, 1982 ; Amit and Brunel, 1997 ; Yakovlev et al, 1998 ; Wong and Wang, 2006 ; Zenke et al, 2015 ; Gillary et al, 2017 ), comparable to selective delay activity observed in the prefrontal cortex when animals are engaged in working memory tasks ( Funahashi et al, 1989 ; Romo et al, 1999 ).…”
Section: Introductionmentioning
confidence: 96%